Letters from students to Liz Case - Pesce, Liz, author; Lobato, Esther M., author (Colorado State University. Libraries, 1995)
Two letters from students thanking Liz Case for talking to their class about World War II.
Keywords: Fashion -- History; Fashion -- Exhibitions